Towards the monitoring of goal 16 of the United Nations' sustainable development goals (SDGS): a study of the selection, rationale and validity of indicators with suggestions for further improvement - Jandl, Michael (Publication series, 2017)
Over the past half-decade, the United Nations has engaged in an unprecedented global, participatory and inclusive consultation process that lead to the definition and adoption of a new set of Sustainable Development Goals (SDGs) as a successor to the earlier Millennium Development Goals (MDGs). After literally hundreds of global, regional and national consultation meetings and countless written submissions and online consultations with inputs from national institutions, civil society organizations, academia, regional and international organizations and the departments and agencies of the UN system debating the merits of a multitude of competing objectives, representatives from UN Member States in a series of intergovernmental negotiations agreed on a common and universal set of goals and targets for the period 2015-2030. This study looks into the process and substance of the debate, based on a review of written sources, interviews with a number of experts involved in the development of the goals, targets and indicators, and inputs from written questionnaires, with a view to learn more about the strengths and weaknesses of the process and its outcomes.The focus of this study is on the development of the global indicator framework for SDG 16, and in particular on indicators relating to rule of law, access to justice and corruption. While there are a number of critical points to be raised about the content and formulation of SDG 16 and its targets, many of which are reviewed in this study, there is a broad consensus among many commentators, as well as the experts interviewed, that the inclusion of a goal on peace, justice and institutions, with a broad number of targets, is a historic achievement by itself and that, generally, the targets within SDG 16 are comprehensive, meaningful and well balanced.